Study of the transition from EHL to BL regions under friction of Ag and Ni. I. Analysis of acoustic emission. (September 2017) - Moshkovich, Alexey; Perfilyev, Vladislav; Lapsker, Igor; Feldman, Yishay; Rapoport, Lev
Abstract: The main goal of this work is the study of the interaction between friction and the AE parameters for materials with different stacking fault energy (SFE) - Ni and Ag. The effects of load on the friction coefficient, wear rate, temperature and AE signals were studied. In order to evaluate a transition from EHL to BL regions, the Stribeck curves were analyzed. It was shown that the waveforms characterize the friction both in the macro scale (contact spot interaction) and microscale (single contact interaction). Low frequency range characterizes mainly shearing and damage in contact spots, while high frequency range indicates single interactions and plastic deformation at these points. The models of friction related to the waveforms in different lubricant conditions are considered. Highlights: Friction, wear and acoustic emission (AE) of Ag and Ni was studied. The transition from the EHL to BL region was analyzed. The interaction between the AE friction and wear parameters was considered. The effect of stacking fault energy on friction and the AE is discussed. The models of friction interaction and waveforms are presented.